2021
DOI: 10.3390/ijms22158308
|View full text |Cite
|
Sign up to set email alerts
|

Amaryllidaceae Alkaloids of Norbelladine-Type as Inspiration for Development of Highly Selective Butyrylcholinesterase Inhibitors: Synthesis, Biological Activity Evaluation, and Docking Studies

Abstract: Alzheimer’s disease (AD) is a multifactorial neurodegenerative condition of the central nervous system (CNS) that is currently treated by cholinesterase inhibitors and the N-methyl-d-aspartate receptor antagonist, memantine. Emerging evidence strongly supports the relevance of targeting butyrylcholinesterase (BuChE) in the more advanced stages of AD. Within this study, we have generated a pilot series of compounds (1–20) structurally inspired from belladine-type Amaryllidaceae alkaloids, namely carltonine A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…The structure of the best AChE/BuChE inhibitor within this study ( 1 ) is displayed in Figure 3 , together with belladine-type AAs. The latest study published by Al Mamun et al [ 80 ] reported synthesis of compounds with the same fundamental unit, but the developed compounds possessed different substitution patterns within the A-ring ( Figure 3 ). Seven compounds of the twenty synthesized possessed a strong and selective h BuChE inhibition profile, with IC 50 values below 1 μM [ 80 ].…”
Section: Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structure of the best AChE/BuChE inhibitor within this study ( 1 ) is displayed in Figure 3 , together with belladine-type AAs. The latest study published by Al Mamun et al [ 80 ] reported synthesis of compounds with the same fundamental unit, but the developed compounds possessed different substitution patterns within the A-ring ( Figure 3 ). Seven compounds of the twenty synthesized possessed a strong and selective h BuChE inhibition profile, with IC 50 values below 1 μM [ 80 ].…”
Section: Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…The latest study published by Al Mamun et al [ 80 ] reported synthesis of compounds with the same fundamental unit, but the developed compounds possessed different substitution patterns within the A-ring ( Figure 3 ). Seven compounds of the twenty synthesized possessed a strong and selective h BuChE inhibition profile, with IC 50 values below 1 μM [ 80 ]. The most potent one showed nanomolar range activity with an IC 50 value of 72 nM and an excellent selectivity pattern over AChE, reaching almost 1400 ( Figure 3 ).…”
Section: Amaryllidaceae Alkaloidsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study demonstrated that norbelladine itself has slight in vitro anti-inflammatory and anti-oxidant properties [ 25 ]. In another study, synthetically designed complex alkaloid derivatives of carltonin A and B of the norbelladine-type were shown to exhibit anti-butyrylcholinesterase (BuChE) and -prolyl oligopeptidase (POP) properties, both of which are considered interesting targets for AD [ 26 , 27 , 28 ]. However, the pharmaceutical properties of norbelladine-type alkaloids in relation to AD, viral infections, and cytotoxicity remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%